A Rare Case Depicting MR Interpretation of Persistent Urachal Remnants in Adults - Ahluwalia, VV; Rawat, A; Narayan, S; Gupta, AK (Nepalese Journal of Radiology, 2014)
Embryonic remnant of the cloaca and the allantois present after birth as a midline fibrous cord is usually detected in infancy and childhood. Failure to obliterate results in urachal disease is rare in adults. Varied remnants of the urachus have been reported. In this case report the usefulness of basic high resolution sonography for initial screening & usefulness of MRI in delineating the length of tract in an adult has been highlighted. DOI: http://dx.doi.org/10.3126/njr.v4i1.11371 Nepalese Journal of Radiology, Vol.4(1) 2014: 56-58